2022
DOI: 10.1021/acsnano.1c09622
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Template-Assisted Assembly of Additive-Free Ti3C2Tx MXene Microlattices with Customized Structures toward High Areal Capacitance

Abstract: Ti3C2T x MXene is a promising material for electrodes in microsupercapacitors. Recent efforts have been made to fabricate MXene electrodes with designed structures using 3D printing to promote electrolyte permeation and ion diffusion. However, challenges remain in structural design diversity due to the strict ink rheology requirement and limited structure choices caused by existing extrusion-based 3D printing. Herein, additive-free 3D architected MXene aerogels are fabricated via a 3D printed template-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 74 publications
0
39
1
Order By: Relevance
“…S18 †). In contrast to the reported weak or rigid MXene architecture (Table S5 †), 24,29,61 as far as we know, this is the rst report on a lightweight and superelastic 3D printed MXene-based aerogel by a delicate trade-off between the rheological and mechanical properties. Overall, the macroscopic skeleton structure and lament microstructure are responsible for the attractive compressive performance.…”
Section: Reversible Compressibility and Fatigue Resistance Of Mxene/ ...contrasting
confidence: 70%
See 1 more Smart Citation
“…S18 †). In contrast to the reported weak or rigid MXene architecture (Table S5 †), 24,29,61 as far as we know, this is the rst report on a lightweight and superelastic 3D printed MXene-based aerogel by a delicate trade-off between the rheological and mechanical properties. Overall, the macroscopic skeleton structure and lament microstructure are responsible for the attractive compressive performance.…”
Section: Reversible Compressibility and Fatigue Resistance Of Mxene/ ...contrasting
confidence: 70%
“…Yang et al reported a 3D printed template-assisted method to produce MXene aerogels at 5–150 mg mL −1 followed by etching the resin template in a concentrated alkaline solution for a long time. 29 Tetik et al fabricated 3D MXene macrostructures by the ice template-assisted 3D printing of MXene dispersions with concentrations of 9–15 mg mL −1 . 30 These methods would inevitably require severe template removal or a specific printing environment, and the loose MXene structures are hard to resist the large structural deformation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize the slurry formulation and microfabrication process, researchers developed a cost-effective extrusion-based 3D printing technique with the capability of complex geometry control. The crucial inks with high viscosities and shear-thinning rheological properties were printed on the substrate through a nozzle. 2D materials such as graphene and MXene have been widely used to formulate suitable inks for 3D MSCs. Graphene is one of the most attractive electrode materials for MSCs because of its good electrical conductivity, high specific surface area, large theoretical capacitance, and promising mechanical properties. In 2015, Sun et al . reported the 3D printed MSC using a highly viscous graphene oxide (GO) ink (20 mg mL –1 ), which was then chemically reduced by HI .…”
Section: Three-dimensional Dense Microelectrodesmentioning
confidence: 99%
“…Reconstruction of the electrode architecture by increasing porosity is employed to improve the energy density from different metrics. [15][16][17][18][19][20] Among these strategies, templating methods (polymer spheres or icetemplates) [15,16] and chemically driven assembly [18] are able to produce electrodes with better electrolyte penetration and considerably fast charging/discharging kinetics; however, the microporous structure (>90% porosity) causes a catastrophic reduction in volumetric capacitance. Introduction of hard spacers such as NbN crystals preserves the high volumetric energy density only in thin electrodes (<10 µm) because of the low porosity induced unsatisfied mass transfer.…”
Section: Doi: 101002/adma202205723mentioning
confidence: 99%